The Influence of E-WOM on Risk Perception and Consumer Trust in the Development of Catfish Farming into Agro-Ecotourism : Case Study on JMK Catfish Farming SMEs in Bojonegoro Regency - Nafisah, A’isy Fiklil; Sudarmiatin (Abadi Institute, 2025)
This study examines the influence of electronic word-of-mouth (e-WOM) on consumer risk perception and trust in the context of developing Micro, Small, and Medium Enterprises (MSMEs) in catfish farming into agro-education tourism in Bojonegoro Regency. The research method used is quantitative, with data collection through questionnaires from 80 respondents. The research results show that e-WOM has a significant influence on risk perception and consumer trust. The implication of these findings is the importance of effective e-WOM management for the development of agro-tourism in SMEs.